PRODUCTION OF PRE-SEXED RACING CAMEL OFFSPRING USING EMBRYO BIOPSY AND DETECTION OF CAMELID SEX SPECIFIC POLYNUCLEIC ACID SEQUENCES - Tinson, A. H.; Harrison, B.; King, B.; Singh, K.; Wade, N.; Reed, K. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text